TMT proteomics of erythroblasts from healthy donors and erythroblasts/ring sideroblasts from MDS-RS patients - Moura, Pedro Luis; Hellström-Lindberg, Eva (Karolinska Institutet, 2023)
This dataset consists of semi-quantitative 10-plex TMT proteomics analysis of FACS-separated bone marrow cells obtained from 3 healthy bone marrow donors and 3 MDS-RS patients. The objective of this data collection was to assess several parameters on how the bone marrow of MDS-RS patients differs from that of healthy donors. The samples included in this analyses were 3 samples of sorted GPA+ erythroblasts pooled from 5 healthy donors (2+2+1) and 3 samples of sorted GPA+ erythroblasts plus 3 samples of purified ring sideroblats from 3 MDS-RS patients.

This dataset includes the raw mass spectra, QC and processed results.

Processing: In short, FACS-separated samples were snap frozen in liquid nitrogen. Cell pellets were lysed with 4 % SDS lysis buffer and prepared for mass spectrometry using a modified version of the SP3 protein clean up and digestion protocol published by Moggridge S. et al 2018.

The following files are included in the dataset:

- Processed data and analysis.xlsx (2.63 MB)
- Variable_list_Processed_data_and_analysis.xlsx (23 KB)
- Readme for raw data .zip file.txt (562 bytes)
- Readme for Processed data.xlsx file (1.07 KB)
- 13553_STD_EAEHPM1_10_TMT10_HiRIEF_3-10pH_20210504_07.15.zip (7.68 GB)

Syftet med denna datainsamling var att bedöma flera parametrar om hur benmärgen hos MDS-RS-patienter skiljer sig från den hos friska donatorer. Denna datauppsättning består av semikvantitativ 10-plex TMT-proteomikanalys av FACS-separerade benmärgsceller erhållna från 3 friska benmärgsdonatorer och 3 MDS-RS-patienter. Se den engelska beskrivningen för mer information.

Datasetet består av följande:

- Processed data and analysis.xlsx (2.63 MB)
- Variable_list_Processed_data_and_analysis.xlsx (23 KB)
- Readme for raw data .zip file.txt (562 bytes)
- Readme for Processed data.xlsx file (1.07 KB)
- 13553_STD_EAEHPM1_10_TMT10_HiRIEF_3-10pH_20210504_07.15.zip (7.68 GB)
TMT proteomikanalys av erytroblaster från friska donatorer och erytroblaster/ringsideroblaster från patienter med MDS-RS
Keywords: Myelodysplastic Syndromes; Myelodysplastiskt syndrom; SF3B1; SF3B1; Myelodysplastic syndromes; myelodysplastiska syndrom; MDS-RS; MDS-RS; Natural Sciences; Naturvetenskap; Biological Sciences; Biologi; Cell Biology; Cellbiologi; Genetics and Genomics; Genetik och genomik; Bioinformatics and Computational Biology; Bioinformatik och beräkningsbiologi; Hematology; Hematologi; Basic Cancer Research; Basal cancerforskning